2009
DOI: 10.1038/jhh.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of candesartan and losartan: a meta-analysis of trials in the treatment of hypertension

Abstract: Informed by the findings from prospective observational studies and randomized outcome trials, guidelines for the management of hypertension acknowledge that the benefit of treatment can be attributed largely to blood pressure (BP) reduction. Therefore, quantification of differential BP lowering of different agents within classes of anti-hypertensives is of practical importance. The objective of this analysis was to compare the efficacy of candesartan and losartan with respect to reduction in systolic and dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…(1) and the associated commentaries (2,3). We are reassured that the author’s meta‐analysis is entirely consistent with a more wide ranging and comparable analysis published over a year ago (4). However, certain aspects of the analyses and the interpretation give us cause for concern.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…(1) and the associated commentaries (2,3). We are reassured that the author’s meta‐analysis is entirely consistent with a more wide ranging and comparable analysis published over a year ago (4). However, certain aspects of the analyses and the interpretation give us cause for concern.…”
supporting
confidence: 80%
“…The potential clinical importance of a 1.96 mmHg difference in diastolic blood pressure (DBP) is based upon cost‐utility analysis utilising a 10‐year Markov model. This ignores epidemiological evidence and findings from outcome trials (4) and fails to acknowledge the 2006 Health Survey for England which suggests that a reduction in 2 mmHg of DBP would save 14,000 lives per annum in the UK (5). Although there are no outcome trials comparing different ARBs, there is no acknowledgement of a study that utilised data from electronic primary care journals and mandatory Swedish national registers for death and hospitalisation, which suggested that, in the treatment of hypertension, there is a BP independent risk reduction in cardiovascular disease with candesartan compared with losartan (6).…”
mentioning
confidence: 99%
“…• A Cochrane review concluded all drugs in the group have a statistically equivalent effect on blood pressure 10 • Small differences in blood pressure lowering effect are likely to be unimportant in clinical practice, where blood pressure is treated to target with diet and exercise as well as drugs [11][12][13] • Losartan costs 43p per month per mm Hg systolic blood pressure reduction (figure⇓)…”
Section: Blood Pressurementioning
confidence: 99%
“…For example, candesartan has a stronger affinity for the receptor and is more effective at lowing BP than losartan. 14,15 This observation may explain the Swedish Heart Failure Registry finding a lower mortality risk associated with candesartan compared with losartan. 16 In this same regard, other studies demonstrated a greater reduction in BP in those treated with olmesartan compared with losartan and valsartan.…”
Section: Discussionmentioning
confidence: 81%
“…18,19 Previous studies showed that candesartan, telmisartan, irbesartan, and olmesartan are superior to losartan in reducing BP. 15,[20][21][22][23][24] The superior antihypertensive effects might explain the slight reduction in the overall mortality of those 4 above-mentioned ARBs. These observations add circumstantial support to the hypothesis that differences in antihypertensive efficacy may account for the differences in mortality risk.…”
Section: Discussionmentioning
confidence: 99%